Sound effect on dynamics and stability of fluid sloshing in zero-gravity - Lukovsky, I.A.; Timokha, A.N. (Інститут гідромеханіки НАН України, 1999)
Theoretical study of acoustic interaction affecting the dynamics and stability of limited fluid volume in zero-gravity is carried out. Two main acoustic effects on a fluid surface are analyzed. The first is the change of dynamic characteristics of fluid sloshing in zero-gravity due to acoustic loading; the second is the movement of a "fluid cork" along the tube (acoustic pumping). Mathematical analysis is based on the averaging of original free interface problem. This allows to reduce a free interface problem to a free boundary problem on surface waves with additional nonlinear terms in the dynamic condition on an unknown surface. Nonlinear phenomena are described per structuring a series of analytical and numerical-analytical solutions. These examples concern the cylindrical vessel with gravity vector along the directrix and, hence, comparison of the results with solutions of capillary problem becomes available. The experimental conclusion that acoustic loads can give rise to equilibrium shapes contrasting to capillary surfaces is confirmed. Also the phenomena of acoustic stabilization and destabilization of "fluid-gas" interface are demonstrated including the case when such a destabilization causes the acoustic pumping.